1987
DOI: 10.1159/000116137
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Computed Tomography and <sup>123</sup>I-HIPDM Scans in Multiple Sclerosis with Large Plaque

Abstract: We report a case of acute multiple sclerosis in whom computed tomography (CT) scan suggested the presence of a large plaque. The anatomical and functional recovery of the brain tissue was followed by means of repeated CT scan and 123I-HIPDM studies. Single photon emission CT may be successfully employed to monitor the pathophysiological changes associated with the demyelinating process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These findings are consistent with the view that decline of cognition is not limited to the chronic-progressive patients or those with severe motor impairment. 47 10 11 The Rey Auditory Verbal Learning test in both the modalities (Short Term and Long Term) was the most sensitive test to elicit memory deficit, while Digit Span was not shown to be significantly impaired. Several studies have shown that short term memory capacity (that is, span memory) appears to be unaffected in MS' 5' suggesting a specific memory problem in the learning ability rather than in retention.5 103 Furthermore, in accordance with a number of previous studies,3 5 9 memory deficit was noted with both verbal and visuospatial material.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with the view that decline of cognition is not limited to the chronic-progressive patients or those with severe motor impairment. 47 10 11 The Rey Auditory Verbal Learning test in both the modalities (Short Term and Long Term) was the most sensitive test to elicit memory deficit, while Digit Span was not shown to be significantly impaired. Several studies have shown that short term memory capacity (that is, span memory) appears to be unaffected in MS' 5' suggesting a specific memory problem in the learning ability rather than in retention.5 103 Furthermore, in accordance with a number of previous studies,3 5 9 memory deficit was noted with both verbal and visuospatial material.…”
Section: Discussionmentioning
confidence: 98%
“…On CT, acute lesions are usually of decreased or normal attenuation with a variable enhancement after injection of a contrast agent [8][9][10][11][12][13]. Destruction of myelin may be associated with cavitation and axonal loss [4].…”
Section: Discussionmentioning
confidence: 99%
“…basis pontis with preservation of axons and cell bodies, without inflammatory cell infiltration or vascular alterations. In about l 0% of patients, extra pontine demyelination is seen in the thalamus, lateral geniculate ganglia, amygdala, cerebellum, basal ganglia, and corpus callosum [8]. The most common associations continue to be alcoholism and malnutrition with liver disease.…”
mentioning
confidence: 99%